1994
DOI: 10.2172/10119073
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved observation of discrete and continuous MHD dynamo in the reversed-field pinch edge

Abstract: This report was prepared as an account of work sponsored by an agency of the United States Government. Neither the United States nor any agency thereof, nor any of their employees, makes any warranty, expressed or implied, or assumes any legal liability or responsibility for any third party's use or the results of such use of any information, apparatus, product or process disclosed in this report, or represents that its use by such third party would not infringe privately owned rights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…where B rec is the reconnecting eld, which i s t ypically the radial eld B r in the RFP. The typical drift parameter can be estimated to be on the order of 0.2-0.3 based on the observation of current carrying fast electrons [Stoneking et al, 1994] or the measured j k , n, and T e [Ji et al, 1994]. Using typical parameters [Ji, Prager, and Sar, 1995] in MST (Madison Symmetrical Torus) plasmas as we shall mention in the next section, i.e., B T = 2kG, n = 1 10 19 =m 3 , T e = 100eV, and the plasma radius a = 0 : 5m, we h a v e =a(1:5-2:5) 10 3 .…”
Section: Relative Rate Of Change In Helicity and Energy A Quantitatimentioning
confidence: 99%
See 1 more Smart Citation
“…where B rec is the reconnecting eld, which i s t ypically the radial eld B r in the RFP. The typical drift parameter can be estimated to be on the order of 0.2-0.3 based on the observation of current carrying fast electrons [Stoneking et al, 1994] or the measured j k , n, and T e [Ji et al, 1994]. Using typical parameters [Ji, Prager, and Sar, 1995] in MST (Madison Symmetrical Torus) plasmas as we shall mention in the next section, i.e., B T = 2kG, n = 1 10 19 =m 3 , T e = 100eV, and the plasma radius a = 0 : 5m, we h a v e =a(1:5-2:5) 10 3 .…”
Section: Relative Rate Of Change In Helicity and Energy A Quantitatimentioning
confidence: 99%
“…In the case of a laboratory plasma (the MST RFP), direct measurements indicated that the turbulence is predominantly electrostatic, thus causing helicity transport in the mean eld with no eects on the turbulent eld. Figure 9 shows such an example of measured helicity ux caused by the electrostatic turbulence [Ji, Prager, and Sar, 1995] together with the measured -eect [Ji et al, 1994].…”
Section: Helicity In Mean and Turbulent Fieldsmentioning
confidence: 99%
“…The resistive slow dynamo term, appearing as the second term of Eq. (20), changes the mean helicity also in the resistive time scale. The electrostatic MHD dynamo and diamagnetic dynamo, both appearing in the surface integral, transport the mean helicity across space while the inductive part of the MHD dynamo − (∂ A/∂t) · B , appearing in the volume integral in the both equations but with opposite signs, converts helicity from the fluctuations to the mean field [46].…”
Section: Magnetic Helicity and Dynamo Effectsmentioning
confidence: 95%
“…The first successful detection [20] of the MHD dynamo in the RFP plasmas was made in the well-controlled Madison Symmetric Torus (MST) plasmas. As discussed in Sec.…”
Section: Measurements Of Dynamo Effectsmentioning
confidence: 99%
See 1 more Smart Citation